1995
DOI: 10.1006/viro.1995.0036
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between RNA-Dependent RNA Polymerase of Alfalfa Mosaic Virus and Its Template: Oxidation of Vicinal Hydroxyl Groups Blocksin VitroRNA Synthesis

Abstract: In the life cycle of a (+)-strand RNA plant virus the processes of template RNA recognition and initiation of the synthesis of a complementary strand by the viral RNA-dependent RNA polymerase (RdRp) are crucial early steps. Using a template-dependent in vitro RNA synthesizing system of alfalfa mosaic virus (AIMV) we were able to study the effect of small chemical modifications of the 3' end of the template RNAs on product formation. After oxidation of the 3'-terminal nucleoside of the template no products coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Although the AMV coat protein co-purifies in polymerase preparations (Quadt et al, 1991), and coat protein has been described as an integral component of the polymerase protein (Degraaff, Thorburn, and Jaspars, 1995), the coat protein-polymerase interaction was not detected in yeast two-hybrid experiments (Van Der Heijden et al, 2001). Technical issues with the yeast two hybrid assay might explain the results, because it was also found that yeast growth was not observed when full-length P1 and P2 proteins were used in the binding and activation domain constructs (Van Der Heijden et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although the AMV coat protein co-purifies in polymerase preparations (Quadt et al, 1991), and coat protein has been described as an integral component of the polymerase protein (Degraaff, Thorburn, and Jaspars, 1995), the coat protein-polymerase interaction was not detected in yeast two-hybrid experiments (Van Der Heijden et al, 2001). Technical issues with the yeast two hybrid assay might explain the results, because it was also found that yeast growth was not observed when full-length P1 and P2 proteins were used in the binding and activation domain constructs (Van Der Heijden et al, 2001).…”
Section: Discussionmentioning
confidence: 99%